Technology of ultrasonic control of gas-shielded welding process; IOP Conference Series: Materials Science and Engineering; Vol. 125 : Materials Treatment: Current Problems and Solutions - Solodsky S. A. Sergey Anatolievich (2016, 2016)
Title screen